Historical rural architecture of North Portugal and Spanish Galicia: local vernacular forms and concept of adaptation, case study of Porreiras - Marta Orszt; Elżbieta Raszeja (Vitruvio: International Journal of Architectural Technology and Sustainability)
Vernacular forms which can be found in North Portugal and Galicia (region of Western Spain) can be traced down up until times, when this geographical area was bound together through Celtic influences. Wood, stone, and clay, used for local constructions, appear in many forms which are until now well preserved around the area. The main objective of research was to identify vernacular forms, focusing on granaries, commonly found in the study area, and creating the proposal of their reuse. Development and roots of those buildings is researched, showing their historical origin, locally sourced materials used in the region, as well as the state of the buildings nowadays and legal ways of their protection in Spain and Portugal. The base of the project was a village renewal concept which aims to adapt the ruins of unused agricultural settlements located in Porreiras for cultural tourism needs, with a proposal of reusing granaries as pilgrim units. Minimal intervention is made thanks to creating interior of a granary as a piece of furniture, filling, but not interfering with existing construction. Concept of safeguarding granaries through giving them new function is proposed to be implemented on Camino de Santiago tail, since the granaries are commonly found in rural landscape of North Portugal and Spanish Galicia.